STRATEGI PENINGKATAN KINERJA PENDIDIK PROFESIONAL BERBASIS ETOS KERJA QURâ€™ANI - Rosidin, Rosidin (J-PAI: Jurnal Pendidikan Agama Islam, 2016)
This paper is the text of the Koran studies aimed at finding Quranic ethos of the key concepts that could potentially improve the quality of professional educators fourth competence, if implemented optimally. In the process, this article refers to the steps of methodological-applicative interpretation Tarbawi practical: to determine the theme, identify the passages relevant, then analyze the data paragraph with three analytical techniques, namely language (lughawi), content (tahlili) and education (Tarbawi ). There are three main findings of this study. First, the "self-awareness" is a key concept work ethic Qur'ani in improving the performance of professional educators. Details, improvement of professional competence through basic awareness of the obligations of educators; improvement of pedagogical competence through an awareness of the human rights of learners; increase awareness of personal competence through for my own shortcomings; improvement of social competence through awareness of the advantages of others. Second, the implementation strategy of self-awareness in improving the performance of professional educators are theological (faith), theoretical (science), practical (charity) and moralistic (morals). Thirdly, there are three levels of quality implementation of self-awareness, which is below the standard (wrongdoers); according to the standard (muqtashid); and above standard (Sabiq).Â Keywords: Self-Awareness, Qur'anic Performance, Professional Educators